Multistage hybrid evolutionary computing-based optimal PMU placement for large scale power grid network. (2018) - Patil, Arunkumar; Girish, V.; Ananthapadmanaba, T.; Kulkarni, A.D.
Phasor measurement unit (PMU) is one of the most significant grid components that plays vital role in ensuring reliable power transmission and distribution. The optimal PMU placement (OPP) in power system can not only ensure grid cost reduction, real-time monitoring and control, but can reduce the operational complexities and overheads significantly. This paper proposes a novel multistage hybrid evolutionary computing scheme for OPP solution. Our proposed model applied adaptive genetic algorithm (AGA) for initial state point retrieval for OPP, which was then fed as input to the pattern search (PS)-based PMU placement optimisation. Our proposed AGA-PS scheme ensures OPP solution by retrieving minimum number of PMUs and its optimal location across grid network to make power system completely observable under varied cases. The simulation results with IEEE 14, IEEE 39, IEEE 118 and KPTCL 155 bus networks has exhibited that the proposed AGA-PS outperforms major existing approaches in terms of optimal OPP solutions.